High human herpesvirus 6 viral load in pediatric allogeneic hematopoietic stem cell transplant patients is associated with detection in end organs and high mortality. (27th November 2017) - Winestone, Lena E.; Punn, Rajesh; Tamaresis, John S.; Buckingham, Julia; Pinsky, Benjamin A.; Waggoner, Jesse J.; Kharbanda, Sandhya
Abstract: Human Herpes Virus 6 (HHV‐6) reactivation occurs in approximately half of patients following allogeneic hematopoietic stem cell transplant (HSCT). While encephalitis and delayed engraftment are well‐documented complications of HHV‐6 following HSCT, the extent to which HHV‐6 viremia causes disease in children is controversial. We performed a retrospective review of HHV‐6 reactivation and possible manifestations in pediatric allogeneic HSCT patients at a single institution. Of 89 children and young adults who underwent allogeneic HSCT over a three‐and‐a‐half‐year period, 34 patients reactivated HHV‐6 early post‐transplant. Unrelated donor stem cell source and lack of antiviral prophylaxis were risk factors for the development of HHV‐6 viremia. Viremia correlated with the presence of acute graft‐versus‐host disease, but not chronic graft‐versus‐host disease. We identified two subgroups within the viremic patients—a high‐risk viremic and tissue‐positive group that reactivated HHV‐6 and had suspected end‐organ disease and a low‐risk viremic but asymptomatic group that reactivated HHV‐6 but did not exhibit symptoms or signs of end‐organ disease. Peak viral load was found to be strongly associated with mortality. Prospective studies in larger numbers of patients are needed to further investigate the role of HHV‐6 in causing symptomatic end‐organ disease as well as the association of viral load with mortality.